Are sugarcane leaf-detritus well colonized by aquatic macroinvertebrates? - Leite-Rossi,Luciene Aparecida (2012)
AIM: The aim was to compare the kinetics of decomposition and the colonization of leaf litter of two plant species, the native Talauma ovata (pinha-do-brejo) and the exotic Saccharum officinarum (sugarcane), by aquatic macroinvertebrates; METHODS: From each substrate, three recipients of colonization were taken from a stream, and the specimens identified to the lowest taxonomic level on days 7, 15, 34, 44, 61 and 75. The debris was weighed at the beginning and end of the experiment and determined their cell wall fractions; RESULTS: The coefficients of mineralization indicated higher velocity decay of organic matter refractory in T. ovata. There was no difference in taxonomic structure of macroinvertebrates, between the two substrates, but the community exhibited distinct functional feeding groups in the peak of colonization, with a greater number of shredders in T. ovata. The successive states of decomposition of the two plant detritus showed distinct macroinvertebrate densities; CONCLUSIONS: The amount and state of the plant biomass were important factors influencing the density and diversity of the macroinvertebrate fauna throughout the process of organic decomposition.